Meningkatkan Kepemimpinan dan Kerja Sama melalui Outdoor Education Camping Program - Rafdlal Saeful Bakhri; Arfin Deri Listiandi; Moh. Nanang Himawan Kusuma; Didik Rilastiyo Budi; Topo Suhartoyo; Rohman Hidayat (JUARA : Jurnal Olahraga, 2020)
Teenagers who are involved in achievement oriented sports tend to focus more on technique and tactics training. Whereas social skills are important aspects in the development of teenagers is often forgotten. Therefore, a program is needed that can develop aspects of social skills, especially leadership and teamwork. This study aims to determine the effect of the application of outdoor education camping programs on improving leadership and teamwork on youth athletes in basketball and futsal clubs. This study uses a quantitative approach with a quasi-experimental method of pretest-posttest design. The number of research subjects were 30 teenage athletes, in Sukabumi basketball and futsal clubs who were selected using cluster random sampling. The instruments used were in the form of a leadership and teamwork questionnaire. The result of research data of the ability and leadership variable gained average score of pretest as amount 52,2 and 56,4 for its posttest. On team work variable is gained average score of pretest 24,4 and 31,16 for its posttest. The results showed that there were positive and significant improvements in leadership skills and teamwork.